Routines of "sitting" and "enjoying ourselves" in the common room of a dementia unit. (2nd January 2019) - Andersen, Elisabeth Muth; Kristiansen, Elisabeth Dalby; Rasmussen, Gitte
Abstract: Purpose: Routinized activities create security for persons with dementia (PWDs) and help care staff manage everyday tasks, but care staff also assist PWDs with constructing routines during their leisure time. This paper investigates how a PWD negotiates how to use the common room in a dementia ward as a social space with co-present staff members, other residents, and a visiting researcher. Methods: Based on ethnographic observations and video recordings and using conversation analytical methodology, the paper presents sequential analyses of video recorded data collected at a dementia unit in a Danish care facility. Results: Detailed analyses of selected instances indicate that the PWD treats care staff as being in charge of the social organization of common room, and they show how the PWD is routinely guided to sit calmly, minding his own business. The analyses also show that the PWD relies on ritualized action and routine activities when managing co-presence and interaction with the visiting researcher. Moreover, they show that a previous non-routine joint activity is used by the PWD to take initiative and thereby re-establish it later. Conclusions: We argue that routine and ritual both provide constraints but also resources for PWDs to actively co-co-create new shared activities with co-present others, and we suggest that PWDs' possibilities for taking initiatives for activities during leisure time among other things rely on the routines that have already been established in interaction with care staff and others or on non-routine activities which PWDs may turn into routines as they re-establish them.